src/HOL/Library/Quotient.thy
changeset 35182 4c39632b811f
parent 35181 92d857a4e5e0
parent 35161 be96405ccaf3
child 35183 8580ba651489
equal deleted inserted replaced
35181:92d857a4e5e0 35182:4c39632b811f
     1 (*  Title:      HOL/Library/Quotient.thy
       
     2     Author:     Markus Wenzel, TU Muenchen
       
     3 *)
       
     4 
       
     5 header {* Quotient types *}
       
     6 
       
     7 theory Quotient
       
     8 imports Main
       
     9 begin
       
    10 
       
    11 text {*
       
    12  We introduce the notion of quotient types over equivalence relations
       
    13  via type classes.
       
    14 *}
       
    15 
       
    16 subsection {* Equivalence relations and quotient types *}
       
    17 
       
    18 text {*
       
    19  \medskip Type class @{text equiv} models equivalence relations @{text
       
    20  "\<sim> :: 'a => 'a => bool"}.
       
    21 *}
       
    22 
       
    23 class eqv =
       
    24   fixes eqv :: "'a \<Rightarrow> 'a \<Rightarrow> bool"    (infixl "\<sim>" 50)
       
    25 
       
    26 class equiv = eqv +
       
    27   assumes equiv_refl [intro]: "x \<sim> x"
       
    28   assumes equiv_trans [trans]: "x \<sim> y \<Longrightarrow> y \<sim> z \<Longrightarrow> x \<sim> z"
       
    29   assumes equiv_sym [sym]: "x \<sim> y \<Longrightarrow> y \<sim> x"
       
    30 
       
    31 lemma equiv_not_sym [sym]: "\<not> (x \<sim> y) ==> \<not> (y \<sim> (x::'a::equiv))"
       
    32 proof -
       
    33   assume "\<not> (x \<sim> y)" then show "\<not> (y \<sim> x)"
       
    34     by (rule contrapos_nn) (rule equiv_sym)
       
    35 qed
       
    36 
       
    37 lemma not_equiv_trans1 [trans]: "\<not> (x \<sim> y) ==> y \<sim> z ==> \<not> (x \<sim> (z::'a::equiv))"
       
    38 proof -
       
    39   assume "\<not> (x \<sim> y)" and "y \<sim> z"
       
    40   show "\<not> (x \<sim> z)"
       
    41   proof
       
    42     assume "x \<sim> z"
       
    43     also from `y \<sim> z` have "z \<sim> y" ..
       
    44     finally have "x \<sim> y" .
       
    45     with `\<not> (x \<sim> y)` show False by contradiction
       
    46   qed
       
    47 qed
       
    48 
       
    49 lemma not_equiv_trans2 [trans]: "x \<sim> y ==> \<not> (y \<sim> z) ==> \<not> (x \<sim> (z::'a::equiv))"
       
    50 proof -
       
    51   assume "\<not> (y \<sim> z)" then have "\<not> (z \<sim> y)" ..
       
    52   also assume "x \<sim> y" then have "y \<sim> x" ..
       
    53   finally have "\<not> (z \<sim> x)" . then show "(\<not> x \<sim> z)" ..
       
    54 qed
       
    55 
       
    56 text {*
       
    57  \medskip The quotient type @{text "'a quot"} consists of all
       
    58  \emph{equivalence classes} over elements of the base type @{typ 'a}.
       
    59 *}
       
    60 
       
    61 typedef 'a quot = "{{x. a \<sim> x} | a::'a::eqv. True}"
       
    62   by blast
       
    63 
       
    64 lemma quotI [intro]: "{x. a \<sim> x} \<in> quot"
       
    65   unfolding quot_def by blast
       
    66 
       
    67 lemma quotE [elim]: "R \<in> quot ==> (!!a. R = {x. a \<sim> x} ==> C) ==> C"
       
    68   unfolding quot_def by blast
       
    69 
       
    70 text {*
       
    71  \medskip Abstracted equivalence classes are the canonical
       
    72  representation of elements of a quotient type.
       
    73 *}
       
    74 
       
    75 definition
       
    76   "class" :: "'a::equiv => 'a quot"  ("\<lfloor>_\<rfloor>") where
       
    77   "\<lfloor>a\<rfloor> = Abs_quot {x. a \<sim> x}"
       
    78 
       
    79 theorem quot_exhaust: "\<exists>a. A = \<lfloor>a\<rfloor>"
       
    80 proof (cases A)
       
    81   fix R assume R: "A = Abs_quot R"
       
    82   assume "R \<in> quot" then have "\<exists>a. R = {x. a \<sim> x}" by blast
       
    83   with R have "\<exists>a. A = Abs_quot {x. a \<sim> x}" by blast
       
    84   then show ?thesis unfolding class_def .
       
    85 qed
       
    86 
       
    87 lemma quot_cases [cases type: quot]: "(!!a. A = \<lfloor>a\<rfloor> ==> C) ==> C"
       
    88   using quot_exhaust by blast
       
    89 
       
    90 
       
    91 subsection {* Equality on quotients *}
       
    92 
       
    93 text {*
       
    94  Equality of canonical quotient elements coincides with the original
       
    95  relation.
       
    96 *}
       
    97 
       
    98 theorem quot_equality [iff?]: "(\<lfloor>a\<rfloor> = \<lfloor>b\<rfloor>) = (a \<sim> b)"
       
    99 proof
       
   100   assume eq: "\<lfloor>a\<rfloor> = \<lfloor>b\<rfloor>"
       
   101   show "a \<sim> b"
       
   102   proof -
       
   103     from eq have "{x. a \<sim> x} = {x. b \<sim> x}"
       
   104       by (simp only: class_def Abs_quot_inject quotI)
       
   105     moreover have "a \<sim> a" ..
       
   106     ultimately have "a \<in> {x. b \<sim> x}" by blast
       
   107     then have "b \<sim> a" by blast
       
   108     then show ?thesis ..
       
   109   qed
       
   110 next
       
   111   assume ab: "a \<sim> b"
       
   112   show "\<lfloor>a\<rfloor> = \<lfloor>b\<rfloor>"
       
   113   proof -
       
   114     have "{x. a \<sim> x} = {x. b \<sim> x}"
       
   115     proof (rule Collect_cong)
       
   116       fix x show "(a \<sim> x) = (b \<sim> x)"
       
   117       proof
       
   118         from ab have "b \<sim> a" ..
       
   119         also assume "a \<sim> x"
       
   120         finally show "b \<sim> x" .
       
   121       next
       
   122         note ab
       
   123         also assume "b \<sim> x"
       
   124         finally show "a \<sim> x" .
       
   125       qed
       
   126     qed
       
   127     then show ?thesis by (simp only: class_def)
       
   128   qed
       
   129 qed
       
   130 
       
   131 
       
   132 subsection {* Picking representing elements *}
       
   133 
       
   134 definition
       
   135   pick :: "'a::equiv quot => 'a" where
       
   136   "pick A = (SOME a. A = \<lfloor>a\<rfloor>)"
       
   137 
       
   138 theorem pick_equiv [intro]: "pick \<lfloor>a\<rfloor> \<sim> a"
       
   139 proof (unfold pick_def)
       
   140   show "(SOME x. \<lfloor>a\<rfloor> = \<lfloor>x\<rfloor>) \<sim> a"
       
   141   proof (rule someI2)
       
   142     show "\<lfloor>a\<rfloor> = \<lfloor>a\<rfloor>" ..
       
   143     fix x assume "\<lfloor>a\<rfloor> = \<lfloor>x\<rfloor>"
       
   144     then have "a \<sim> x" .. then show "x \<sim> a" ..
       
   145   qed
       
   146 qed
       
   147 
       
   148 theorem pick_inverse [intro]: "\<lfloor>pick A\<rfloor> = A"
       
   149 proof (cases A)
       
   150   fix a assume a: "A = \<lfloor>a\<rfloor>"
       
   151   then have "pick A \<sim> a" by (simp only: pick_equiv)
       
   152   then have "\<lfloor>pick A\<rfloor> = \<lfloor>a\<rfloor>" ..
       
   153   with a show ?thesis by simp
       
   154 qed
       
   155 
       
   156 text {*
       
   157  \medskip The following rules support canonical function definitions
       
   158  on quotient types (with up to two arguments).  Note that the
       
   159  stripped-down version without additional conditions is sufficient
       
   160  most of the time.
       
   161 *}
       
   162 
       
   163 theorem quot_cond_function:
       
   164   assumes eq: "!!X Y. P X Y ==> f X Y == g (pick X) (pick Y)"
       
   165     and cong: "!!x x' y y'. \<lfloor>x\<rfloor> = \<lfloor>x'\<rfloor> ==> \<lfloor>y\<rfloor> = \<lfloor>y'\<rfloor>
       
   166       ==> P \<lfloor>x\<rfloor> \<lfloor>y\<rfloor> ==> P \<lfloor>x'\<rfloor> \<lfloor>y'\<rfloor> ==> g x y = g x' y'"
       
   167     and P: "P \<lfloor>a\<rfloor> \<lfloor>b\<rfloor>"
       
   168   shows "f \<lfloor>a\<rfloor> \<lfloor>b\<rfloor> = g a b"
       
   169 proof -
       
   170   from eq and P have "f \<lfloor>a\<rfloor> \<lfloor>b\<rfloor> = g (pick \<lfloor>a\<rfloor>) (pick \<lfloor>b\<rfloor>)" by (simp only:)
       
   171   also have "... = g a b"
       
   172   proof (rule cong)
       
   173     show "\<lfloor>pick \<lfloor>a\<rfloor>\<rfloor> = \<lfloor>a\<rfloor>" ..
       
   174     moreover
       
   175     show "\<lfloor>pick \<lfloor>b\<rfloor>\<rfloor> = \<lfloor>b\<rfloor>" ..
       
   176     moreover
       
   177     show "P \<lfloor>a\<rfloor> \<lfloor>b\<rfloor>" by (rule P)
       
   178     ultimately show "P \<lfloor>pick \<lfloor>a\<rfloor>\<rfloor> \<lfloor>pick \<lfloor>b\<rfloor>\<rfloor>" by (simp only:)
       
   179   qed
       
   180   finally show ?thesis .
       
   181 qed
       
   182 
       
   183 theorem quot_function:
       
   184   assumes "!!X Y. f X Y == g (pick X) (pick Y)"
       
   185     and "!!x x' y y'. \<lfloor>x\<rfloor> = \<lfloor>x'\<rfloor> ==> \<lfloor>y\<rfloor> = \<lfloor>y'\<rfloor> ==> g x y = g x' y'"
       
   186   shows "f \<lfloor>a\<rfloor> \<lfloor>b\<rfloor> = g a b"
       
   187   using assms and TrueI
       
   188   by (rule quot_cond_function)
       
   189 
       
   190 theorem quot_function':
       
   191   "(!!X Y. f X Y == g (pick X) (pick Y)) ==>
       
   192     (!!x x' y y'. x \<sim> x' ==> y \<sim> y' ==> g x y = g x' y') ==>
       
   193     f \<lfloor>a\<rfloor> \<lfloor>b\<rfloor> = g a b"
       
   194   by (rule quot_function) (simp_all only: quot_equality)
       
   195 
       
   196 end